Picking bakeapples on a mash - Branch Cultural Historical Association (2007)
The mashes around Branch are great places to pick the luxurious bakeapple as well as the lesser known mash berry. Some mashes around Branch include the Big Mash, the Salmon Hole Mash, Catamaran Mash and Yellow Mash. Betsy Hennesseys mash was Mrs. Hennesseys (YEARS) favourite place to pick bakeapples. While the wet ground of mashes is good for bakeapples, other berries like blueberries and partridge berries grow on higher, drier terrain.